REIMAGINING ENGLISH LANGUAGE TEACHING THROUGH MULTILITERACIES PEDAGOGY: A SCOPING REVIEW OF EMPIRICAL STUDIES (2015–2025) - Rinekso, Aji Budi; Rianawati, Rianawati; Gustine, Gin Gin; Musthafa, Bachrudin; Kadaryanto, Budi (Universitas Muhammadiyah Metro, 2026)
Multiliteracies pedagogy addresses complex communication issues in the digital world by promoting diverse literacy practices, multimodal meaning-making, and critical engagement with texts. Many studies have explored how multiliteracies pedagogy is applied in language learning from multiple perspectives, yet comprehensive reports remain limited. To address this gap, this scoping review synthesizes empirical studies on the implementation of multiliteracies pedagogy in English language teaching across primary, secondary, and tertiary education. Guided by PRISMA framework, 526 records were retrieved from the Taylor & Francis database, selected for its extensive coverage of Scopus-indexed journals in humanities and applied linguistics. Based on predefined inclusion and exclusion criteria, 23 articles published between 2015 and 2025 were included in the final analysis. The analysis identified seven key themes: identity and cultural expression; multimodality and technology integration; multiliteracies and pedagogical innovation; power, equity, and resistance; language and academic literacy development; challenges in implementing multiliteracies pedagogy; and intercultural understanding and global English. Findings reveal that multiliteracies pedagogy supports learner identity, inclusivity, intercultural awareness, and academic development, while also indicating gaps in geographical coverage, primary-level research, and methodological diversity. This review complements previous studies by providing a cross-level synthesis of empirical research across different educational contexts.